A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
PLEASE HELP
The table shows the solution to the equation 2x − 3 − 1 = 2:
Step 1 2x − 3 = 2 + 1
Step 2 2x − 3 = 3
Step 3 2x − 3 = 3 or 2x + 3 = 3
Step 4 2x = 6 or 2x = 0
Step 5 x = 3 or x = 0
Which is the first incorrect step?
Step 1
Step 3
Step 5
Solution is correct
anonymous
 one year ago
PLEASE HELP The table shows the solution to the equation 2x − 3 − 1 = 2: Step 1 2x − 3 = 2 + 1 Step 2 2x − 3 = 3 Step 3 2x − 3 = 3 or 2x + 3 = 3 Step 4 2x = 6 or 2x = 0 Step 5 x = 3 or x = 0 Which is the first incorrect step? Step 1 Step 3 Step 5 Solution is correct

This Question is Closed

ganeshie8
 one year ago
Best ResponseYou've already chosen the best response.1Hint \[\large \heartsuit=3~~~ \implies~~ \heartsuit=3~~\text{or}~~\heartsuit=3\]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0ok. I see what ur putting down. Its C isnt it

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0yes thats what i mean.. b

ganeshie8
 one year ago
Best ResponseYou've already chosen the best response.1Yes Step 3 2x − 3 = 3 or 2x + 3 = 3 has a mistake
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.